Sociodemographic indicators and quality of life of caregivers of children with neuromotor changes - Lucena, Neide Maria Gomes de; Brito, Patrícia Meireles; Felipe, Rafaela Vitória Pereira; Lira, Eliene Martins de; Lira, Natália Gonçalves de; Rodrigues, Susana Lígia da Silva; Barros, Maria de Fátima Alcântara; Carvalho, Antônio Geraldo Cidrão de; Araújo, Maria das Graças Rodrigues de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Children with neuromotor changes are challenged daily, and such challenges may be faced with the help of a caregiver. Thus, the functional dependence of these children lead to the daily demands, causing physical and emotional distress, which affect the quality of life of their caregiver. Objective: Analyze the sociodemographic indicators that interfere with the level of life quality of the caregivers of children with neuromotor changes. Method: 50 caregivers of children with neuromotor changes were interviewed at the Association of Parents and Friends of the Exceptional (APAE) of Paraiba, on the city of João Pessoa. To evaluate the quality of life, the questionnaire SF-36 was used, in addition to collecting demographic data (sex, age, degree of kinship, marital status, number of children, school level and religion). For the data analysis, a descriptive study was developed, the normality test of Shapiro-Wilk was realized, followed by the inferential analysis with non-parametric correlation of Spearman, considering the significant value α = 0.05. Results: There was a predominance of the female sex (96%) with medium age of ≥ 39 years old. Correlating the sociodemographic indicators with the level of life quality of the SF-36 of the caregivers, only the vitality domain presented significance with the variables: number of children (p=0.012), benefits (p=0.044), and how the transfer of the child is done (p=0.044). There was no significant difference relating the sociodemographic indicators on the other domains. Conclusion: The knowledge of sociodemographic indicators that interfere with the quality of life shows the importance of preventive measures, such as guidance and, if needed, treatment for improvement of possible grievances.